2006
DOI: 10.1109/tem.2005.861804
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and outcomes of strategic IS alignment: an empirical investigation

Abstract: Abstract-Prior research argues that alignment between business and information systems (IS) strategies enhances organizational performance. However, factors affecting alignment have received relatively little empirical attention. Moreover, IS strategic alignment is assumed to facilitate the performance of all organizations, regardless of type or business strategy. By using two studies of business firms and academic institutions, this paper: 1) develops and tests a model relating alignment, its antecedents, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
343
1
38

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(402 citation statements)
references
References 61 publications
(121 reference statements)
20
343
1
38
Order By: Relevance
“…In addition, the existence of clear business plans influenced both short-term and long-term alignments. In another study, Chan et al (2006) examined antecedents to alignment directly under the control of IT management (such as shared domain knowledge, planning sophistication, and the credibility of the IT group due to prior IT success), and factors external to the IT group such as organizational size and environmental uncertainty. In earlier research, Brown and Magill (1994) identified antecedents such as corporate vision, strategic IT role, satisfaction with management of technology, satisfaction with the use of technology, and the locus of control for system approvals.…”
Section: Antecedents To Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the existence of clear business plans influenced both short-term and long-term alignments. In another study, Chan et al (2006) examined antecedents to alignment directly under the control of IT management (such as shared domain knowledge, planning sophistication, and the credibility of the IT group due to prior IT success), and factors external to the IT group such as organizational size and environmental uncertainty. In earlier research, Brown and Magill (1994) identified antecedents such as corporate vision, strategic IT role, satisfaction with management of technology, satisfaction with the use of technology, and the locus of control for system approvals.…”
Section: Antecedents To Alignmentmentioning
confidence: 99%
“…Lederer and Mendelow (1989) found that coordination of the IT plan and the business plan were achieved in three dimensions (Shank et al, 1973): plan content, timing, and personnel. Chan et al (2006) found that planning sophistication or comprehensiveness led to an increase in shared knowledge, which in turn affected alignment. The more sophisticated the planning process, the greater the likelihood of involvement of personnel from different areas of expertise.…”
Section: Foreground Antecedents/behaviorsmentioning
confidence: 99%
“…CFMs can be used as a sophisticated planning tool that increases shared domain knowledge [4]. However, they do not replace the role of designers.…”
Section: Discussionmentioning
confidence: 99%
“…In case such set is inconsistent (e.g. a same technical context appears with ranges [0,2] and [3,4]), manual analysis is required. Each core set of technical contexts defines the minimal requirements for an IT infrastructure supporting business context BC.…”
Section: Problem 3 (High-variability) Given Bc Which Is the Minimal mentioning
confidence: 99%
See 1 more Smart Citation